Pelatihan Sport Massage Berbasis Anatomi Fungsional sebagai Upaya Meningkatkan Kompetensi Pelatih Cabang Olahraga Prestasi - Meyke Parengkuan (Universitas Negeri Gorontalo, 2026)
Sports coaches play an important role in supporting athletes' recovery through the application of sports massage. However, many coaches in Gorontalo City still have limited competence in anatomy-based sports massage. This community service program aimed to improve coaches' knowledge and practical skills through theory- and practice-based training. The program employed a participatory training approach consisting of lectures, demonstrations, hands-on practice, mentoring, and evaluation using a pretest-posttest design, observation, and participant satisfaction questionnaires. The results showed an increase in participants' average knowledge score from 58.4 to 84.6, with an N-Gain score of 0.63 (moderate category). Observation results indicated that more than 80% of participants were able to correctly perform sports massage techniques based on functional anatomy principles. Participants also expressed highly positive responses regarding the training materials, learning methods, and program benefits. The training successfully improved coaches' competence and produced a functional anatomy-based sports massage module that can be sustainably used to support athlete development programs.